STUDI EFISIENSI PASAR MODAL SYARIAH INDONESIA: OVER-REAKSI ATAU MOMENTUM? [STUDY OF THE EFFICIENCY OF INDONESIAN SHARIA CAPITAL MARKET: OVER-REACTION OR MOMENTUM?] - Perdana Wahyu Santosa; Nurul Huda (Universitas Pelita Harapan, 2020)
In the bearish, islamic equity market condition of 15.6% due to the depreciation of the IDR-USD exchange rate by 10.8%, during March 2018-March 2019, respectively. The decline in the IDR exchange rate was triggered by the Federal Reserve Bank's policy of a reference interest rate of 25 basis points. The method used uses the overreaction market hypothesis. The sample stock used is a member of the Jakarta Islamic Index (JII) at Indonesia Stock Exchange with an observation period of 55 weeks. This overreaction analysis is divided in two stages: (i) formation of a winner-loser portfolio, (ii) testing the overreaction-momentum hypothesis. Findings: in (i) 10-week test period: overreaction, (ii) 20-week test period: momentum, (iii) 30-week test period: momentum; (iv) 40-week test period: overreaction; (v) 55 week test period: overreaction. It was concluded that overreaction occurred at the beginning of the market experiencing bearish due to the high shock effect, then the market began to be consistent until there was a pattern of momentum in two continued periods, but the momemtum pattern ended again at the 40th week and the overreaction pattern happened again at the end of the bearish period.Abstrak dalam Bahasa Indonesia. Pada saat pasar modal syariah mengalami penurunan yang tajam (bearish) 15.6% akibat terdepresiasinya nilai tukar IDR-USD sebesar 10.8%, periode Maret 2018-Maret 2019. Penurunan nilai tukar IDR tersebut dipicu oleh kebijakan Federal Reserve Bank yang meanikkan suku bunga acuan sebesar 25 basis poin. Metode yang digunakan menggunakan overreaction market hypothesis. Sampel saham yang digunakan merupakan anggota Jakarta Islamic Index (JII) di Bursa Efek Indonesia dengan periode observasi selama 55 minggu. Analisis overreaksi ini dilakukan dalam dua tahap yaitu: (i) pembentukan portofolio winner-loser, (ii) pengujian hipotesis overreaksi-momentum. Temuan: pada (i) uji periode 10 minggu: overreaksi, (ii) uji periode 20 minggu: momentum, (iii) uji periode 30 minggu: momentum; (iv) uji periode 40 minggu: overreaksi; (v) uji periode 55 minggu: overreaksi. Disimpulkan bahwa overreaksi terjadi pada awal pasar mengalami bearish karena efek kejut yang tinggi, kemudian pasar mulai konsisten hingga terjadi pola momentum pada dua periode lanjutan, namun kembali pola momemtum berakhir pada minggu ke-40 dan pola overreaksi terjadi kembali pada akhir periode bearish.